Insight-HXMT observations of Swift J0243.6+6124: the evolution of RMS pulse fractions at super-Eddington luminosity. Issue 4 (17th August 2020) - Wang, P J; Kong, L D; Zhang, S; Chen, Y P; Zhang, S N; Qu, J L; Ji, L; Tao, L; Ge, M Y; Lu, F J; Chen, L; Song, L M; et al.
ABSTRACT: Based on Insight-HXMT data, we report on the pulse fraction evolution during the 2017–2018 outburst of the newly discovered first Galactic ultraluminous X-ray (ULX) source Swift J0243.6+6124. The pulse fractions of 19 observation pairs selected in the rising and fading phases with similar luminosity are investigated. The results show a general trend of the pulse fraction increasing with luminosity and energy at supercritical luminosity. However, the relative strength of the pulsation between each pair evolves strongly with luminosity. The pulse fraction in the rising phase is larger at luminosity below 7.71 × 10 38  erg s −1, but smaller at above. A transition luminosity is found to be energy independent. Such a phenomenon is first confirmed by Insight-HXMT observations and we speculate that it may have relation with the radiation-pressure-dominated accretion disc.